Arctic-midlatitude weather linkages in North America - Overland, James E.; Wang, Muyin (Polar Science, 2018)
There is intense public interest in whether major Arctic changes can and will impact midlatitude weather such as cold air outbreaks on the central and east side of continents. Although there is progress in linkage research for eastern Asia, a clear gap is conformation for North America. We show two stationary temperature/geopotential height patterns where warmer Arctic temperatures have reinforced existing tropospheric jet stream wave amplitudes over North America: a Greenland/Baffin Block pattern during December 2010 and an Alaska Ridge pattern during December 2017. Even with continuing Arctic warming over the past decade, other recent eastern US winter months were less susceptible for an Arctic linkage: the jet stream was represented by either zonal flow, progressive weather systems, or unfavorable phasing of the long wave pattern. The present analysis lays the scientific controversy over the validity of linkages to the inherent intermittency of jet stream dynamics, which provides only an occasional bridge between Arctic thermodynamic forcing and extended midlatitude weather events. journal article